Environmental development in Brazilian companies: The role of human resource management - Jabbour, Charbel Jose Chiappetta [UNESP]; Jabbour, Ana Beatriz Lopes [UNESP]; Teixeira, Adriano Alves [UNESP]; Freitas, Wesley Ricardo S. [UNESP] (Elsevier, 2012)
Specialized literature states that proper environmental management at companies requires support from human resource management. This occurs because the more efficient and effective human resource management is, the more it tends to contribute towards the organization's objectives. Considering that environmental management is an emerging organizational objective, human resource practices, when efficient and effective, tend to incorporate environmental goal and to become greener. In order to contribute to this emerging field of research, this paper reports on an empirical study about the relationship between human resources and environmental management at 75 Brazilian companies. The data collected were analyzed statistically using Structural Equation Modeling. The main results indicated that human resource management practices tend to statistically significant relate to environmental management at analyzed companies, through validation of H 1, but his relationship can be considered weak. © 2012 Elsevier B.V.
Keywords: Brazil; Environmental management; Green human resource management; Human resources